Compositional signature of trace elements in stream sediments along the Babahoyo/Daule riverbeds (Ecuador): A geostatistical and Bayesian approach - Cabrera, Marlon (2024)
The high concentration of potencially toxic elements (PTEs) in stream sediments may pose a significant threat since the pollutants may travel long distances to the sea, affecting aquatic environments and public health. When rivers cross large cities, minning, or cultivated areas, it is usually observing an increasing concentration of PTEs downstream, reachiong hazardeous levels due to the ability and persistence oh heavy metals by bioaccumulation in the enviromnent.